Message - Mahadeva Rao, Dr. U. S. (Universal Journal of Pharmaceutical Research, 2018)
It is great honor and privilege for me to be appointed as Member - Editorial Board, Universal Journal of Pharmaceutical Research (UJPR). My heartiest salutations to Prof. Dr. Kapil Kumar, Editor-in-Chief and the other board members for their accomplishment of today through their hard work and persistence. Indeed, UJPR is now recognized as an international rather than a domestic journal with a considerable proportion of manuscripts being contributed from outside the country. UJPR will continue to adhere to its original philosophy of promoting the sharing of basic medical science experience by our members. I believe that the most critical components of any scientific journal's success are the submission of high-quality manuscripts, the dedication of members of its editorial board, and excellence of those reviewing the manuscripts. We will take utmost care for rigorous peer review of all submitted manuscripts to accept only quality contents without any fringe of conflict for publication. I will take this opportunity to appeal to all authors to prepare their manuscripts strictly according to journal instructions so as to avoid any undue delay in its editorial processing and disappointment of rejection. Now we are in the epoch of Cross disciplinary research based publications within the (preclinical) boulevards which usually assimilates information, data, techniques, tools, perspectives, concepts and / or theories from two or more disciplines of focused knowledge to progress rudimentary understanding or to decipher glitches whose solutions are outside the scope of a single discipline or area of research practice. Interdisciplinarians publish the manuscripts by mixing the best elements of disciplinary insights by crossing their parent discipline in order to generate a more wide-ranging appreciation of the issue at hand. Interdisciplinary publication allows for the synthesis of ideas and the synthesis of characteristics from many fields. Hopefully, UJPR Chief with support from editorial team will strive to generate an impact factor for which we invite submission of more original articles and citation of relevant literature published in this journal in your future publications.